Genetic diversity based on agronomic and fruit quality traits in gboma eggplant (Solanum macrocarpon L.) - Adeniji, OT; Kusolwa, PM; Reuben, SWOM (Bangladesh Journal of Agricultural Research, 2018)
Solanum macrocarpon L is a fruit and leaf vegetable in sub-Sahara Africa. The genetic diversity of the crop remains largely unexploited consequently there is a dearth of genetic information on agronomic and fruit quality traits. Agronomic and fruit quality variability and association among traits were evaluated. Twenty – six accessions were grown in a randomized complete block design with three replications. Measurements taken on agronomic and fruit quality traits were subjected to a combined analysis of variance, Principal Component Analysis and grouping using Unweighted Pair Group Method Arithmetic Average using option Ward’s. There were significant differences (P≤0.05) among the accessions for all the traits, while Genotype by Year Interaction (GYI) showed insignificant effects for most traits except plant height at flowering and maturity and seed yield. High broad sense heritability suggested the preponderance of both additive and non-additive genetic action for agronomic and fruit quality traits. The percentage contribution of agronomic traits toward the genetic diversity was maximum in plant height at flowering and plant height at maturity. Positive correlation coefficients was recorded between days to 50% flowering and fruit infructescence/plant (r = 0.45, P≤ 0.05). Dendogram analysis revealed three distinct groups with overlap of traits and no relationship between geographic location and phenotypic diversity. Hybridization among MM 268, MM 10256, MM 150 and MM 10161 may bring together gene constellations for earliness, fruit yield and delayed time to fruit browning. Superior genotypes are recommended for use in hybridization schemes for variety development and the subsequent molecular characterization Bangladesh J. Agril. Res. 43(1): 25-38, March 2018